Energy evolution and infrared radiation characteristics of different bedded coal under uniaxial compression - Guoning ZHANG; Yixin ZHAO; Yuandong SUN; Zhixin GONG (Meitan kexue jishu)
In order to study the energy evolution and infrared radiation response characteristics during the deformation and failure process of coal with different bedding angles, uniaxial compression tests with four different bedding angles (0°, 30°, 60° and 90°) were carried out on a strong burst liability coal samples from 3-1 coal seam of Hongqinghe coal mine. The infrared temperature field characteristics of the coal samples during deformation and damage were monitored using an infrared thermal imaging camera. The test results show that as the bedding angle increases the compressive strength and strain energy of the sample show a “V” shaped trend, reaching the minimum value at 60°. The bedding has a significant impact on the elastic strain Ue in the pre-peak stage and dissipation energy Ud in the post-peak stage; The coal samples showed an overall warming trend with different bedding angles, with an average infrared temperature precursor point of 0.84σp.The bedding structure seriously affects the infrared radiation temperature and the difference of failure patterns lead to different temperature ranges. The 0° and 30° specimens are dominated by shear-tension composite failure, with a high temperature rise of 1.12 and 1.30 ℃, respectively, while the 60° specimen is dominated by single shear failure, with a low temperature rise of 0.46 ℃. The failure of 90° specimen is tensile failure, and the temperature rise is the lowest 0.4 ℃. The strain energy was positively correlated with the mean IR radiation temperature, and the correlation degree was ranked as U<Ue<Ud. The research results can provide reference for early warning of coal dynamic disasters.